Keterkaitan Spasial Produksi Ikan Tawar dan Dampak Sosial-Ekonomi Masyarakat di Kabupaten Magelang - Nuryadin, Didi; Umaroh, Rodhiah; Sodik, Jamzani (Jurnal Ekonomi dan Pembangunan Indonesia, 2024)
This research analyzes the spatial correlation between freshwater aquaculture production in Magelang Regency and the social and economic welfare of the community. Utilizing the Indeks Moran, LISA, and bivariate LISA methods, the results indicate inter-district correlations in freshwater fish production with a clustered distribution pattern. Mungkid and Muntilan districts are identified as production centers and hotspots. Freshwater fish production is also associated with community welfare, showing correlations with farmer groups despite a scattered distribution. However, the analysis of freshwater fish production and freshwater fish-based SMEs reveals a strong spatial relationship, particularly in Mungkid district, a central area fostering local development.